MAKE A WEBSITE IN JAVA AND BALI MOUNTAINS USING MACROMEDIA DREAMWEAVER MX - Rudi Alamsyah; Melani Dewi Lusita, SKom., MMSI (Jurnal Sistem Informasi, 2004)
World of technology in Indonesia is currently very rapid, especially in information technology and information society will also need a fast, accurate and actual is needed by society at large. A lot of the information media here the author chose the Internet information media which has been a subject matter in this writing. This explains the scientific writing about mountain information website design in Java and Bali by using Macromedia Dreamweaver MX Application Program, the author will explain how the process to design and organize documents in a "Website Mountains" that can be easily understood the intent and purpose built this website.